Avaliação da carbonatação em concretos com cinza do bagaço da cana-deaçúcar - Agassi, Joenilson Daniel (2011)
The need for renewable sources boosts the production of alcohol in the world, mainly in Brazil, which has the highest production of both ethanol and sugar, the ideal weather and high technology also contribute, making Brazil the largest producer of substitute fuel to fuels derived from petroleum. In its manufacturing process occurs the generation of a by-product, bagasse used from the sugar and alcohol sector companies in the co-generation power, which has as a secondary waste the ash from the sugar cane bagasse (SCB). This residue can be used as a fine aggregate in the production of concrete and mortar, thus minimizing the extraction of natural resources, preserving the river banks and contributing to the proper disposal of that residue. This study aims to evaluate the influence of the SCB in concrete properties when used as fine aggregate partially replacing the natural sand, through the study of the resistance to compression and carbonation. The concrete was produced with CPV-ARI Portland cement, sand of quartz origin and crushed stone of basaltic origin, and the sand was partially replaced by SCB in the levels of 0, 5, 10, 15, 20, 25, 30, 40 and 50% in mass. The test results from the compression resistance showed that there was an increasing to the replacement of sand by SCB up to 25% compared to the reference concrete (0%), with a level of 20% the one which gained more resistance , 6.6% above the standard. The results of statistical analysis of the accelerated carbonation front showed that the concrete with the less depassivation was the one containing 15% of SCB, with a carbonation front of 67.8% less than the standard concrete. It was also found that there was a decrease in the carbonated layer in the concrete with replacement up to 30% of sand by the SCB. This study is trying to clarify some doubts about the durability of concrete containing SCB and provides a safe alternative of fine aggregates replacement for civil construction.